(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
For better or worse, art always has political repercussions, yet the link between ethics and aesthetics is often uncomfortable. Over time, highly refined strategies have been developed to neutralize its emancipatory potential. The analysis starts from afar, from the "Fight for art" which took place in Germany at the end of the 1920s and from the actions of the GAAG Guerilla Art Action Group, carried out from 1969 onwards, to arrive at the present that has seen protest actions take shape and spread precisely because they are built around powerful artistic communications, such as the performance Un violador en tu camino, which from Chile travelled around the world.